1997
DOI: 10.1086/303696
|View full text |Cite
|
Sign up to set email alerts
|

The Soft X‐Ray Properties of a Complete Sample of Optically Selected Quasars. II. Final Results

Abstract: We present the Ðnal results of a ROSAT PSPC program to study the soft X-ray emission properties of a complete sample of low-z quasars. This sample includes all 23 quasars from the Bright Quasar Survey with z ¹ 0.400 and cm~2. Pointed ROSAT PSPC observations were made for all N H I Gal \ 1.9 ] 1020 quasars, yielding high signal-to-noise (S/N) spectra for most objects, which allowed an accurate determination of the spectral shape. The following main results were obtained :1. The spectra of 22 of the 23 quasars a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

66
727
4
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 527 publications
(800 citation statements)
references
References 86 publications
66
727
4
1
Order By: Relevance
“…Based on ROSAT data, Boller, Brandt, & Fink (1996) and Laor et al (1997) found a significant correlation between the X-ray photon indexes of radio-quiet AGNs and the value for the FWHM H , where those AGNs with the narrowest broad Balmer lines, narrow-line Seyfert 1 galaxies (NLS1s), tended toward the steep end of the distribution of C. Subsequent work with ASCA in the 2-10 keV band has extended this finding to higher energy, although the spread of C in the 2-10 keV band is much smaller (e.g., Brandt, Mathur, & Elvis 1997;Reeves & Turner 2000). Mrk 231 has relatively narrow Balmer emission lines, FWHM H ¼ 2870 km s À1 (Boroson & Meyers 1992) and FWHM H ¼ 3000 km s À1 (Lípari, Terlevich, & Macchetto 1993), particularly for a QSO of its luminosity.…”
Section: X-ray Variability and Spectral Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on ROSAT data, Boller, Brandt, & Fink (1996) and Laor et al (1997) found a significant correlation between the X-ray photon indexes of radio-quiet AGNs and the value for the FWHM H , where those AGNs with the narrowest broad Balmer lines, narrow-line Seyfert 1 galaxies (NLS1s), tended toward the steep end of the distribution of C. Subsequent work with ASCA in the 2-10 keV band has extended this finding to higher energy, although the spread of C in the 2-10 keV band is much smaller (e.g., Brandt, Mathur, & Elvis 1997;Reeves & Turner 2000). Mrk 231 has relatively narrow Balmer emission lines, FWHM H ¼ 2870 km s À1 (Boroson & Meyers 1992) and FWHM H ¼ 3000 km s À1 (Lípari, Terlevich, & Macchetto 1993), particularly for a QSO of its luminosity.…”
Section: X-ray Variability and Spectral Resultsmentioning
confidence: 99%
“…A large, negative ox indicates relatively weak soft X-ray emission; the mean value of ox for radio-quiet QSOs is %À1.48 (e.g., Laor et al 1997) with a typical range from À1.7 to À1.3 for objects that do not suffer from X-ray absorption (e.g., Brandt, Laor, & Wills 2000). Weakness in soft X-rays is plausibly explained by intrinsic X-ray absorption, which strongly depresses the observed flux at low-to-moderate energies.…”
Section: Extended Galaxy Emissionmentioning
confidence: 99%
“…ASCA observations of iron lines in Seyfert 1s (Nandra et al 1997) indicate that the emitting matter is generally neutral and then that the accretion rate does not exceed about 0.1-0.2 the critical value (according to the model of Matt, Fabian & Ross 1993). On the other hand, high accretion rates have been suggested by (Laor et al 1997) to be the basic explanation for the the Narrow Line Seyfert 1s phenomenon (Boller, Brandt & Fink 1996). In TON S 180 BeppoSAX has actually detected such an ionized line (Comastri et al 1998 and this volume), lending support to this hypothesis.…”
Section: Neutral or Ionized Matter?mentioning
confidence: 98%
“…A particularly well-covered broad-band spectrum available is the composite spectrum of quasars (Laor et al 1997) shown in Fig. 1.…”
Section: Examples Of Spectra and Corresponding Standard Disk Modelsmentioning
confidence: 99%